Impact of an educational nursing intervention in patients with copd - Alves, Renata Camargo [UNESP]; Lima, Luciane Soares de; Barbosa, Dulce Aparecida; Lima, Silvana Andrea Molina [UNESP]; Bettencourt, Ana Rita de Cássia (Universidade de Estado do Rio de Janeiro, 2019)
Objective: to evaluate the immediate effects of the orientation of the hospital discharge plan for patients with COPD. Method: prospective and comparative study performed in a private hospital in São Paulo, with patients with COPD. In first step it was used the questionnaire Educational Plan for COPD patients” to assess patient knowledge about their disease. In second step, educational intervention was carried out and in the third, again the of the questionnaire was used. The comparison between pre and post-test results was done by paired T-test. The project was approved by the research ethics committee. Result: from the 50 patients who participated in study, 68% reported not knowing their disease well before orientation and only 22% after educational intervention. In all sections of questionnaire there was an increase in correct answers after educational intervention. Conclusion: the orientation of the hospital discharge plan was effective resulting in an immediate improvement of knowledge.
Impacto de una intervención educativa de enfermería en pacientes con epoc
Impacto de uma intervenção educacional de enfermagem em pacientes portadores de dpoc
Keywords: Chronic obstructive; Education; Health education; Nursing; Patient discharge; Pulmonary disease